2021
DOI: 10.31584/jhsmr.2021843
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Chronic Neck Pain on Respiratory Functions among Female University Students

Abstract: Objective: Students with chronic neck pain have several issues that could constitute susceptibility to respiratory dysfunction. So, this current study was conducted to investigate the impact of chronic neck pain on respiratory function among female university students.Material and Methods: In this cross-sectional study, 60, female University students voluntarily participated, and were divided into two groups: 30 students with chronic idiopathic neck pain (age=21.9±2.2 years, height=160.7±6.5 cm, weight=71.9±8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In developing countries, mechanical neck pain is most common in university students. 4 A study conducted by Gharib and Hamid 5 in Saudi Arabia showed that the prevalence rate of cervical pain among female university students was 54%.…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, mechanical neck pain is most common in university students. 4 A study conducted by Gharib and Hamid 5 in Saudi Arabia showed that the prevalence rate of cervical pain among female university students was 54%.…”
Section: Introductionmentioning
confidence: 99%